2012
DOI: 10.5173/ceju.2012.03.art12
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after botulinum toxin A (BTX-A) injection into the detrusor for treatment of neurogenic detrusor hyperactivity in children

Abstract: PurposeTo prove the long-term efficacy of BTX-A injection in the management of children with neurogenic detrusor hyperactivity.Materials and methods28 out of 145 children with neurogenic bladder (15 male and 13 female, mean age 10.7 years) who were treated between 2002 and 2010 and became non-responders to conservative treatment were included into the retrospective study.We injected 10-12 U/kg of BTX-A (Botox®) into the detrusor at 20-30 sites, sparing the trigone. The mean follow-up was 48 months (range 6-84 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Nine studies out of 12 gave information about adverse events. There were no perioperative urinary tract infections in six studies . Three studies reported post‐injections urinary tract infections, rates ranging from 4% to 29% .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Nine studies out of 12 gave information about adverse events. There were no perioperative urinary tract infections in six studies . Three studies reported post‐injections urinary tract infections, rates ranging from 4% to 29% .…”
Section: Resultsmentioning
confidence: 94%
“…Maximum detrusor pressure (Pdetmax) was evaluated in eight of the series included and was significantly reduced in all of them . These results were observed 1 month after injection with a persistent reduction at 6 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of this paper report data from a retrospective analysis done in a single center with significant experience [1, 2]. The idea behind their work is to assess the efficacy of treatment with botulinum toxin, using a significantly lower dose, in patients with neurogenic or idiopathic detrusor overactivity.…”
mentioning
confidence: 99%